Habitação colaborativa para idosos: uma arquitetura para o envelhecimento ativo - Maestrelli, Heloíse Serro (2018)
The increase in the life expectancy of the population and their aging are realities, and demand adequate infrastructure so that the third age has quality of life in the dwelling. The current reality offers the elderly, who do not have family support, two ways, the first is to maintain their independence by living alone at the cost of solitude, and the second is institutionalization, where the individual loses his autonomy and privacy. This research aims at a solution in which the elderly maintains an active social life and, at the same time, their independence. It also seeks to investigate the role of housing in the search for active aging, providing mental, social and physical health by inducing the elderly to a full, healthy and productive life. It was necessary to study the profile of the elderly and their Brazilian social context, seeking to know what are the shortcomings of the processes of aging. In addition to analyzing successful case studies in the world that contribute to the deepening of the peculiarities inherent to this social group. After this analysis, a Collaborative Housing for the Elderly is proposed.